2014
DOI: 10.1371/journal.pgen.1004257
|View full text |Cite
|
Sign up to set email alerts
|

A LINE-1 Insertion in DLX6 Is Responsible for Cleft Palate and Mandibular Abnormalities in a Canine Model of Pierre Robin Sequence

Abstract: Cleft palate (CP) is one of the most commonly occurring craniofacial birth defects in humans. In order to study cleft palate in a naturally occurring model system, we utilized the Nova Scotia Duck Tolling Retriever (NSDTR) dog breed. Micro-computed tomography analysis of CP NSDTR craniofacial structures revealed that these dogs exhibit defects similar to those observed in a recognizable subgroup of humans with CP: Pierre Robin Sequence (PRS). We refer to this phenotype in NSDTRs as CP1. Individuals with PRS ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 53 publications
(75 reference statements)
0
47
0
1
Order By: Relevance
“…Examples of these include the transcription factors IRF6 (Kondo et al, 2002; Leslie et al, 2013), GRH3 (Peyrard-Janvid et al, 2014), DLX6 (Wolf et al, 2014), FOXE (Ludwig et al, 2014), and PAX7 (Leslie et al, 2015); the guidance signaling molecule Netrin1 (Leslie et al, 2015); the metalloprotease ADAMTS20 (Wolf et al, 2015); and the FGF signaling receptor FGFR2 (Leslie et al, 2015). Almost all of the genes so far identified (with the notable exception of IRF6 (Nehyba et al, 2009)) have clear orthologs in Nasonia (JAL personal observation), holding out the possibility of a conserved molecular basis between CL/P and the facial clefting we see in Nasonia hybrids.…”
Section: Resultsmentioning
confidence: 99%
“…Examples of these include the transcription factors IRF6 (Kondo et al, 2002; Leslie et al, 2013), GRH3 (Peyrard-Janvid et al, 2014), DLX6 (Wolf et al, 2014), FOXE (Ludwig et al, 2014), and PAX7 (Leslie et al, 2015); the guidance signaling molecule Netrin1 (Leslie et al, 2015); the metalloprotease ADAMTS20 (Wolf et al, 2015); and the FGF signaling receptor FGFR2 (Leslie et al, 2015). Almost all of the genes so far identified (with the notable exception of IRF6 (Nehyba et al, 2009)) have clear orthologs in Nasonia (JAL personal observation), holding out the possibility of a conserved molecular basis between CL/P and the facial clefting we see in Nasonia hybrids.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a LINE-1 retrotransposition event into the c-myc gene has been identified in a canine transmissible venereal tumor (180, 181), although it remains uncertain if the insertion event is involved in tumorigenesis. Likewise, LINE-1 retrotransposition events into the Factor IX, dystrophin , and DLX6 genes are implicated in a mild case of hemophilia B in German Wirehaired Pointers, Duchenne-like muscular dystrophy in the Pembroke Welsh Corgi breed, and cleft palate and mandibular abnormalities in the Nova Scotia Duck Tolling Retriever breed (182184). …”
Section: Transposable Elements In Mammalian Genomesmentioning
confidence: 99%
“…Genes in these pathways are shown to affect orofacial clefting in humans [8], which is also well described in animal models [9–11]. Research on a canine model of Pierre Robin Sequence revealed that a LINE-1 insertion in the homologue to the human DLX6 gene is responsible for cleft palate and associated mandibular abnormalities [12]. Sequencing of DLX5 and DLX6 in a cohort of humans with isolated cleft palate has shown causal effects of missense mutations in DLX5 .…”
Section: Animal Studiesmentioning
confidence: 99%